2021
DOI: 10.3390/vaccines9080931
|View full text |Cite
|
Sign up to set email alerts
|

Early Adverse Events between mRNA and Adenovirus-Vectored COVID-19 Vaccines in Healthcare Workers

Abstract: Mass vaccination campaigns are important to control the COVID-19 pandemic, however, adverse events (AEs) contribute to vaccine hesitancy. To investigate and compare early AEs between the BNT162b2 mRNA and AZD1222 adenovirus-vectored vaccines, recipients completed daily surveys about local and systemic reactions for 7 days after each dose, respectively. A total of 80 and 1440 healthcare workers received two doses of BNT162b2 and a first dose of AZD1222 vaccines. Any AEs were reported by 52.5% of recipients afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
2
5
2
Order By: Relevance
“…High rates of nonallergic reactions from 3.4 to 14% were also reported in several recent cohort studies of physician-observed COVID-19 vaccine-related reactions in healthcare workers. Interestingly, as in our cohort, no anaphylaxis cases were observed [23,24]. In contrast, Shavit et al, reporting on the physician-observed safety of mRNA-based COVID-19 vaccines in an Israeli cohort of 429 allegedly high-risk patients, defined as a history of drug or vaccine-induced anaphylaxis or history of allergy to multiple triggers, reported an anaphylaxis incidence of 0.3% (1/429).…”
Section: Discussioncontrasting
confidence: 71%
“…High rates of nonallergic reactions from 3.4 to 14% were also reported in several recent cohort studies of physician-observed COVID-19 vaccine-related reactions in healthcare workers. Interestingly, as in our cohort, no anaphylaxis cases were observed [23,24]. In contrast, Shavit et al, reporting on the physician-observed safety of mRNA-based COVID-19 vaccines in an Israeli cohort of 429 allegedly high-risk patients, defined as a history of drug or vaccine-induced anaphylaxis or history of allergy to multiple triggers, reported an anaphylaxis incidence of 0.3% (1/429).…”
Section: Discussioncontrasting
confidence: 71%
“…We reject the null for the younger age groups 0–15 and 16–54, and do not reject the null for the remaining three elder age groups, regardless of gender. The conclusion of our methods is more reasonable because it is line with the finding in Wi et al (2021), which reveals that there is no sex difference in the occurrence of AEs among elderly people.…”
Section: Real Data Analysissupporting
confidence: 90%
“…After exclusion of 340 irrelevant articles based on title or abstract, 96 articles were subjected to full-text screening of which 84 were eligible to be included in the review ( Supplementary Figure S3 and Table S8). Forty-three of these articles concerned cross-sectional studies (51.2%) ( 12 , 13 , 17 – 57 ), 26 were prospective cohort studies (31.0%) ( 2 , 5 , 14 , 58 80 ), eight retrospective cohort studies (9.5%) ( 81 88 ) and seven were other types of studies ( 6 , 89 94 ) (8.3%). The majority of the studies were performed in Europe (n=26, 31.0%), in Asia (n=24, 28.6%) and in the Middle East (n=21, 25.0%).…”
Section: Resultsmentioning
confidence: 99%